What shifts did COVID-19 year 2020 bring to the labour market in Europe? - Stijn Baert (Institute of Labor Economics (IZA), 2021)
This letter discusses the evolution of key labour market indicators in the EU-27 countries between 2019 and 2020, i.e. between the year before the COVID-19 crisis broke out and the year in which it impacted the economy heavily. Whereas earlier policy-oriented studies have dealt with the evolution of unemployment in 2020, often country by country, this letter focuses on the evolution of unemployment as well as inactivity across European countries. Indeed, previous crises have typically lead not only to more unemployment but also to larger numbers of discouraged unemployed and thus more inactivity. It appears that the Southern European countries, in particular, recorded increases in inactivity, while the Baltic States experienced higher unemployment. In many other countries, unemployment and inactivity remained remarkably stable despite COVID-19.
Keywords: J64; J08; J23; J24; J68; 330; unemployment; inactivity; employment; COVID-19; iceberg decomposition; disincentive effect